2012
DOI: 10.4067/s0718-19572012000200004
|View full text |Cite
|
Sign up to set email alerts
|

Body size structure, biometric relationships and density of Chiton albolineatus (Mollusca: Polyplacophora) on the intertidal rocky zone of three islands of Mazatlan Bay, SE of the Gulf of California

Abstract: Resumen.-Las poblaciones del molusco poliplacóforo Chiton albolineatus fueron estudiadas en 6 sitios con diferente acción del oleaje en el litoral rocoso de 3 islas de la bahía de Mazatlán, en el sureste del golfo de California. Esta especie de quitón es endémico de las costas mexicanas del Pacífico. Para determinar sus patrones demográficos basados en su densidad y tamaño corporal se realizaron muestreos en sitios expuestos y protegidos al oleaje de la zona intermareal de estas islas de enero a diciembre de 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 13 publications
0
11
1
6
Order By: Relevance
“…Perhaps these stages are not adequate for all polyplacophorans, but they are at least for the family Chitonidae, which generally exhibits a common “adult”-size above 40 mm, including the chitons here studied [65], and also shows concordance with the modal size-class exhibited by other Mexican populations of both chitons [44]–[47].…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Perhaps these stages are not adequate for all polyplacophorans, but they are at least for the family Chitonidae, which generally exhibits a common “adult”-size above 40 mm, including the chitons here studied [65], and also shows concordance with the modal size-class exhibited by other Mexican populations of both chitons [44]–[47].…”
Section: Discussionmentioning
confidence: 73%
“…But just toward the adult stage (TL>40 mm), the b-values move downwards to between 2.9 and 2.2 for C. articulatus [43]–[45], and around 2.7 for C. albolineatus [47]. Therefore, this indicates that these species have first, during the early life stages, an isometric growth and subsequently an allometric growth (i.e., growth whereby parts of the same organism grow at different rates) as they develop into adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The central benefits of the relaxation technique, fixation, conservation, and dissection of specimens were successful since relaxed and well-stretched polyplacophorans were obtained. description of ratios by the variations in body shape, 'body outline' (Schwabe 2010), to support separation among species through a curvature index (Mannering 1974), length-weight relationship (Hunter and Brown 1965;Flores-Campaña et al 2012;Avila-Poveda 2013), among many studies requiring a totally relaxed polyplacophoran. Other studies in polyplacophorans describe a relaxation process prior to taking measurements using a solution of magnesium chloride as anaesthetizer (Barnes 1972;Matsumura and Kuwasawa 1996).…”
Section: Discussionmentioning
confidence: 99%
“…There are global reports concerning Class POLYPLACOPHORA on a taxonomic scope and geographical distribution such as [5][6][7][8] for the American Pacific as [9,10], as well as those made in the Mexican coast zone as [3,4,[11][12][13]; other studies also found Chitons' ecological data as [14][15][16]. With respect to marine priority coastal regions in the State of Guerrero, [17] reported for Marine Priority Region No. 32.…”
Section: Introductionmentioning
confidence: 99%